2020
DOI: 10.1016/j.ymben.2020.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Mixing and matching methylotrophic enzymes to design a novel methanol utilization pathway in E. coli

Abstract: One-carbon (C1) compounds, such as methanol, have recently gained attention as alternative low-cost and non-food feedstocks for microbial bioprocesses. Considerable research efforts are thus currently focused on the generation of synthetic methylotrophs by transferring methanol assimilation pathways into established bacterial production hosts. In this study, we used an iterative combination of dry and wet approaches to design, implement and optimize this metabolic trait in the most common chassis, E. coli. Thr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…It seems that FrmA is not the unique GD-Faldh in E. coli, as it was shown that production of formate also occurs in the ∆frmA E. coli strain. It was suggested that a promiscuous alcohol dehydrogenase could replace GD-Faldh activity in the conversion of formaldehyde to S-formyl-GSH, which is then converted to formate by Fgh (Figure 2) [101]. Moreover, two paralogous genes encode Fgh: frmB and yeiG.…”
Section: Modification Of Formaldehyde Dissimilation Pathways In Nonmethylotrophic Bacteria Is a Prerequisite For Synthetic Methylotrophymentioning
confidence: 99%
See 4 more Smart Citations
“…It seems that FrmA is not the unique GD-Faldh in E. coli, as it was shown that production of formate also occurs in the ∆frmA E. coli strain. It was suggested that a promiscuous alcohol dehydrogenase could replace GD-Faldh activity in the conversion of formaldehyde to S-formyl-GSH, which is then converted to formate by Fgh (Figure 2) [101]. Moreover, two paralogous genes encode Fgh: frmB and yeiG.…”
Section: Modification Of Formaldehyde Dissimilation Pathways In Nonmethylotrophic Bacteria Is a Prerequisite For Synthetic Methylotrophymentioning
confidence: 99%
“…In recent times, the development of novel assimilation pathways has received increasing interest, with some of these promising alternative pathways described here. The dihydroxyacetone (DHA) synthase (DAS) pathway is a cyclic formaldehyde assimilation pathway designed using in silico modelling [101]. It was built starting with the tool Find-Path to identify the most efficient pathway for E. coli to consume methanol [101,153].…”
Section: Novel Pathways For Assimilation Of Formaldehydementioning
confidence: 99%
See 3 more Smart Citations